Aberrant tumor vasculature. Facts and pitfalls - Ribatti, Domenico (Frontiers in Pharmacology, 2024)
Endothelial cells form a single cell layer lining the inner walls of blood vessels and play critical roles in organ homeostasis and disease progression. Specifically, tumor endothelial cells are heterogenous, and highly permeable, because of specific interactions with the tumor tissue environment and through soluble factors and cell-cell interactions. This review article aims to analyze different aspects of endothelial cell heterogeneity in tumor vasculature, with particular emphasis on vascular normalization, vascular permeability, metabolism, endothelial-tomesenchymal transition, resistance to therapy, and the interplay between endothelial cells and the immune system.